Candidate pathway-based genetic association study of Platinum and Platinum-Taxane Related Toxicity in a Cohort of Primary Lung Cancer Patients - Johnson, Cassandra (J Neurol Sci, 2015)
BACKGROUND: Chemotherapy-induced peripheral neuropathy (CIPN) is a common toxicity secondary to chemotherapy. Genetic factors may be important in predisposing patients to this adverse effect. PATIENTS AND METHODS: We studied 950 primary lung cancer patients, who received platinum or platinum-combination drug chemotherapy and who had DNA available for study. We analyzed epidemiological risk factors in 279 CIPN patients and 456 non-CIPN patients and genetic risk factors in 141 CIPN patients and 259 non-CIPN patients. The risk factors studied included demographic, diagnostic, and treatment data, as well as 174 tag SNPs (single nucleotide polymorphisms) across 43 candidate genes in the glutathione, cell cycle, DNA repair, cell signaling, and apoptosis pathways. RESULTS: Patients who had diabetes mellitus were more likely to have CIPN (p=0.0002). Other epidemiologic risk factors associated with CIPN included number of cycles (p=0.0004) and type of concurrent chemotherapy (p<0.001) . SNPs most associated with CIPN were in glutathione peroxidase 7 (GPX7) gene (p values 0.0015 and 0.0028, unadjusted and adjusted) and in ATP-binding cassette sub-family C member 4 (ABCC4) gene (p values 0.037 and 0.006, unadjusted and adjusted). We also found other suggestive associations in methyl-o-guanine-methyl-transferase (MGMT) and glutathione-S-transferase (GST) isoforms. CONCLUSIONS: Epidemiological and genetic risk factors associated with CIPN in this cohort, included the type of chemotherapy drug, intensity of chemotherapy treatment, and genes known to be associated with chemotherapy resistance. These findings suggest that differentiating between cytotoxic and neurotoxic mechanisms of chemotherapy drugs is challenging but represents an important step toward individualized therapy and improving quality of life for patients.